How should we interrogate the hypothalamic-pituitary-adrenal axis in patients with suspected hypopituitarism? - Garrahy, Aoife (BMC Endocr Disord, 2016)
Hypopituitarism is deficiency of one or more pituitary hormones, of which adrenocorticotrophic hormone (ACTH) deficiency is the most serious and potentially life-threatening. It may occur in isolation or, more commonly as part of more widespread pituitary failure. Diagnosis requires demonstration of subnormal cortisol rise in response to stimulation with hypoglycemia, glucagon, ACTH(1-24) or in the setting of acute illness. The choice of diagnostic test should be individualised for the patient and clinical scenario. A random cortisol and ACTH level may be adequate in making a diagnosis in an acutely ill patient with a suspected adrenal crisis e.g. pituitary apoplexy. Often however, dynamic assessment of cortisol reserve is needed. The cortisol response is both stimulus and assay- dependent and normative values should be derived locally. Results must be interpreted within clinical context and with understanding of potential pitfalls of the test used.